2013
DOI: 10.1111/fwb.12280
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate assemblages of pools in arid‐land streams have high functional redundancy and are resistant to severe drying

Abstract: Summary Seasonal droughts are predictable components of arid‐land stream hydrology, and many arid‐land aquatic taxa have adapted to their extreme environment. However, climate change is altering this predictable hydrology, producing longer and more severe droughts and creating novel disturbance regimes for resident organisms. The hydrologic transitions from flowing stream to fragmented pools to dry stream bed are frequently associated with steep decreases in taxonomic and functional diversity, referred to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 47 publications
6
101
2
Order By: Relevance
“…Poff et al (2006) recognized that only a limited number of unique trait states are represented in stream macroinvertebrate assemblages having high functional redundancy (Bêche & Resh, 2007;Bêche & Statzner, 2009;Brown & Milner, 2012). In agreement with this finding, Boersma et al (2014) demonstrated experimentally that due to high functional redundancy, drying did not affect functional richness or functional diversity of stream macroinvertebrates. Mueller et al (2013) also argued that functional diversity measured through trait (state-) richness shows limited variability.…”
Section: How Functional Diversity Is Related To Taxonomic Diversity?mentioning
confidence: 54%
See 2 more Smart Citations
“…Poff et al (2006) recognized that only a limited number of unique trait states are represented in stream macroinvertebrate assemblages having high functional redundancy (Bêche & Resh, 2007;Bêche & Statzner, 2009;Brown & Milner, 2012). In agreement with this finding, Boersma et al (2014) demonstrated experimentally that due to high functional redundancy, drying did not affect functional richness or functional diversity of stream macroinvertebrates. Mueller et al (2013) also argued that functional diversity measured through trait (state-) richness shows limited variability.…”
Section: How Functional Diversity Is Related To Taxonomic Diversity?mentioning
confidence: 54%
“…In 2014, almost all reviewed papers used Rao's quadratic entropy for measuring functional diversity of freshwater macroinvertebrates (e.g. Boersma et al, 2014;Feld et al, 2014;Kovalenko et al, 2014;Lange et al, 2014;Vaz et al, 2014).…”
Section: Measuring Functional Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of freshwater ponds and streams are ephemeral or intermittent, which alters connectivity and habitat size, with consequences for species with varying reliance on water (e.g., amphibians, invertebrates) [125,126]. For instance, severe drought extirpated top predators in desert streams in Arizona, USA, allowing mesopredators to increase through release from competition [83].…”
Section: Persistence Of Landscape Structurementioning
confidence: 99%
“…Some macroinvertebrate taxa can exhibit resistance to moderate 61 drought conditions; however, when drying is more severe, their abundance and biomass 62 decreases sharply (Boulton 2003;Boersma et al 2014). Similarly, a study examining the 63 response of multiple species of fish found that survival rates were high during the initial phases 64 of drying, but decreased sharply when drying was more pronounced (Larimore et al 1959).…”
mentioning
confidence: 99%